EFEK ANTIINFLAMASI EKSTRAK ETANOL DAUN LAMUN (Enhalus acoroides) TERHADAP MENCIT (Mus musculus) JANTAN YANG DIINDUKSI KARAGEN - Muhammad Yusuf; Putri Indah Sari; Awaluddin Wijaya (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
This study aimed to determine the anti-inflammatory effect of seagrass (Enhalus acoroides) leaves on male mice (Mus musculus). The type of research used is the RAL method (completely randomized design). Male mice (Mus musculus) were divided into 5 treatment groups including group 1 being mice given 1% Na.CMC suspension as a negative control, group 2 being mice given seagrass leaf extract (Enhalus acoroides) 75 mg/kgBW, group 3 being mice. given 100 mg/kgBW of seagrass leaf extract (Enhalus acoroides), group 4 was mice given 125 mg/kgBW of seagrass leaf extract (Enhalus acoroides) and group 5 was mice given 50 mg of diclofenac sodium as a positive control. The anti-inflammatory test was induced with 1% carrageenan, the volume of edema that occurred after treatment was measured by dipping it into a plestimometer for every 30, 60, 90, 120 minute intervals for 7 days. After that, the percentage decrease in the edema volume parameter was observed. The data were analyzed using the One Way Anova test and continued with the LSD post hoc test. The ethanolic extract of seagrass (Enhalus acoroides) leaves showed that it could reduce the volume of edema in the feet of mice (Mus musculus) at concentrations of 75 mg/kgBW, 100 mg/kgBW, and 125 mg/kgBW by showing a significant difference with the negative control group (p < 0.05). The anti-inflammatory effect of the ethanolic extract of seagrass (Enhalus acoroides) leaves on male mice (Mus musculus) showed effective results in reducing the volume of edema in the legs of mice (Mus musculus).